2015
DOI: 10.1016/j.ajpath.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Continuous Exenatide Infusion Does Not Cause Pancreatic Inflammation and Ductal Hyperplasia in Non-Human Primates

Abstract: In this study, we aimed to evaluate the effects of exenatide (EXE) treatment on exocrine pancreas of nonhuman primates. To this end, 52 baboons (Papio hamadryas) underwent partial pancreatectomy, followed by continuous infusion of EXE or saline (SAL) for 14 weeks. Histological analysis, immunohistochemistry, Computer Assisted Stereology Toolbox morphometry, and immunofluorescence staining were performed at baseline and after treatment. The EXE treatment did not induce pancreatitis, parenchymal or periductal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…An increasing amount of evidence suggests pancreatic safety with GLP‐1 receptor agonists. A recent controlled study with exenatide demonstrated no effect on exocrine pancreatic histology (in baboons) . Moreover, the largest case–control study to date found no adverse effects of exenatide .…”
Section: Discussionmentioning
confidence: 95%
“…An increasing amount of evidence suggests pancreatic safety with GLP‐1 receptor agonists. A recent controlled study with exenatide demonstrated no effect on exocrine pancreatic histology (in baboons) . Moreover, the largest case–control study to date found no adverse effects of exenatide .…”
Section: Discussionmentioning
confidence: 95%
“…A recent histology study by Ueberberg et al in a distinct donor cohort including patients with and without history of incretin based‐treatment (1 GLP‐1R agonist and 6 DPP‐4 inhibitor treated), also found no advanced PanIN lesions in any of the samples studied . Another study showed that continuous, 14‐week infusion of exenatide in non‐human primates does not alter PanIN prevalence . For the present study samples, the average age within the cohort of 7 DPP‐4 inhibitor donors combined with a single GLP‐1R agonist‐treated donor is significantly higher than their non‐incretin‐based counterparts (58.0 ± 10.2 vs 42.3 ± 13.7; P = .0052).…”
Section: Discussionmentioning
confidence: 99%
“…primates does not alter PanIN prevalence. 23 For the present study In the present study, the frequency of GLP-1R-positive cells located within or in close proximity to the ductal epithelium was quantitated. The area of this population of cells with respect to ductal epithelial cells was calculated to be approximately 4%.…”
Section: Glp-1r Expression In Panin1 Areasmentioning
confidence: 99%
“…However, since the start of incretin-based medicine several case reports on the development of acute pancreatitis have been published, and the US Food and Drug Administration (FDA) has issued a "black box warning" for these drugs [81]. Incretin-induced pancreatitis and subsequent oncogenesis have been suggested by some animal studies [82][83][84][85], but the results are conflicting [86][87][88][89][90]. It has also been shown that the GLP-1 receptor is expressed in some but not all pancreatic exocrine cells [91], while DPP-4 is expressed in some (~30%) duct cells [92].…”
Section: Pancreatic Fat Beta-cell Function and Glucose Intolerancementioning
confidence: 99%